Application of the Think-Pair-Share Cooperative Learning Model Building Maintenance Materials to Improve Student Learning Outcomes for Class XI KGSP SMKN 2 Kendari - nawar (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
The study aimed to improve the learning outcomes of class XI students of KGSP SMKN 2 Kendari inbuilding maintenance subjects by applying the Think-Pair-Share (TPS) type cooperative learning model. Thistype of research is classroom action research. The students studied were students of class XI KGSP SMKN 2Kendari with 25 students. The implementation of classroom action research consists of 2 cycles. Each cycle iscarried out according to the changes to be achieved according to what has been designed in the investigatedfactors. The procedures for this classroom action research are (1) planning; (2) implementation of actions; (3)observation and evaluation; and (4) reflection. The data sources of this research are students and teachers. Thedata types are quantitative and qualitative data through observation sheets and learning outcomes tests. How tocollect data about the implementation conditions of the Think-Pair-Share (TPS) cooperative learning model wastaken using teacher and student observation sheets. Data about learning outcomes were taken using a learningoutcome test evaluation tool. The research results show that the learning outcomes of class XI KGSP SMKN 2Kendari students in the building maintenance subject can be improved through the application of the Think-PairShare(TPS) type of cooperative learning model. In the implementation of the second cycle classically, 22 students scored 70 (88.0%). This achievement has increased compared to the classical first cycle of students who scored 70 as many as 17 people (68.0%).